Moci Tegal di Mata Siswa untuk Menjaga Warisan Leluhur - Utami, Desi; Naam, Muh. Fakhrihun; Sugiarto, Eko (CV. ITTC INDONESIA, 2024)
The tradition of moci, which is drinking teapot tea, has a deep meaning for the Tegal community and has been passed down from generation to generation. This study examines students' views on the moci tradition and its role in maintaining ancestral heritage. Through interviews and observations, it was found that for Tegal students, moci is not only a daily habit, but also a symbol of cultural identity that needs to be preserved. This tradition teaches the values of togetherness, openness, and simplicity that are important in their social life. In addition, moci also serves as a means of strengthening social relations in schools and communities. The students play an active role as agents of cultural preservation, by teaching and introducing the moci tradition to other young people through various cultural activities and social media. This research shows that students' efforts in maintaining the moci tradition not only strengthen their cultural identity, but also ensure that the values continue to evolve and are relevant in the modern context.